ASEAN 4.0. ERA: DEVELOPMENT IN DIGITAL ECONOMY AND TRADE SECTOR - Henike Primawanti; Agus Subagyo; Windy Dermawan (Universitas Jenderal Ahmad Yani, 2022)
The ASEAN Free Trade Area (AFTA) is the first step towards economic liberalization in Southeast Asia. Through AFTA, ASEAN member countries reduce to abolish tariffs on certain products in regional trade schemes. AFTA is a facility for the government to regulate what products will be exported and imported in accordance with applicable tariff rules, it makes the community very dependent on the government and large companies for these products. As technology develops and Southeast Asia's population grows, a digital era is formed in the trade sector that promotes more dynamic e-commerce. E-commerce makes people not dependent on the government and more independent in regional markets. Because it covers each individual and MSME with the convenience of digitalized cross-border transactions. The existence of e-commerce caused the trend to change, from where initially the community was very dependent on the government to becoming independent of the products set by the government. This study uses a qualitative-descriptive method with data collection techniques from literature studies from books, journals, official websites, and so on. The results of the study indicate that there has been a change in the trend of trade in ASEAN. This trend is due to the occurrence of digital transformation which provides opportunities for the MSME community to enter regional and global trade. Participation in regional trade in ASEAN is not only followed by state actors but also enlivened by non-state actors, especially all levels of ASEAN society who take advantage of developing e-commerce platforms. Keywords: Transformation, Digital, E-Commerce, Trade, ASEAN